(untitled) (Journal of the College of Basic Education, 2022)
This study sheds light on the historical period that Iraq went through, extending between the years 1933-1937, which witnessed serious fateful events, the most prominent of which was the death of King Faisal I, which caused an imbalance in the political balance, and the exacerbation of political competition between veterans, as well as dealing with the ministries that It was formed during this historical period and the political instability during its reign. This study relied on important historical documents from the files of the royal court, as well as Arabic and Arabized books, letters, treatises, and what was written about this period.